Implementation of School Information Systems Using the CodeIgniter Framework - Muhamad Zuhan Aminurrohman; Arizona Firdonsyah (Universitas Muhammadiyah Sidoarjo, 2021)
The development of Information and Communication Technology is growing rapidly. The need to obtain information quickly and easily encourages people to create better information and communication technologies. The development of this technology has affected all sectors, including in the world of education. Education in Indonesia shows a low quality because some schools still do not take advantage of technological developments. Therefore, schools in Indonesia must start updating school management to create efficient and more advanced management, including the use of the school information system. School Information System is an information system that helps in managing school information. The method used is a literal study by looking at and comparing existing research. The expected result of this research is a website-based school information system.